2003
DOI: 10.1023/b:jocm.0000025279.27084.39
|View full text |Cite
|
Sign up to set email alerts
|

Computer Keyboard and Mouse as a Reservoir of Pathogens in an Intensive Care Unit

Abstract: The colonization rate for computer keyboard and mouse of a PDMS with potentially pathogenic microorganisms is greater than that of other user interfaces in a surgical ICU. These fomites may be additional reservoirs for the transmision of microorganisms and become vectors for cross-transmission of nosocomial infections in the ICU setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 11 publications
1
78
1
1
Order By: Relevance
“…Several studies have reported contamination of these objects and their possible role in the transmission of HAIs [9][10][11][12][13][14][15][16][17][18]. Our study, unlike others, considered all these items together in a hospital setting, as well as comparing units with different organization, patient turnover, medical personnel, and visitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported contamination of these objects and their possible role in the transmission of HAIs [9][10][11][12][13][14][15][16][17][18]. Our study, unlike others, considered all these items together in a hospital setting, as well as comparing units with different organization, patient turnover, medical personnel, and visitors.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare equipment is frequently shared between hospital staff, who may have different hygiene practices. Medical devices (stethoscopes, otoscopes, and thermometers) and various objects in hospital environments, such as telephones and computers, have been associated with transmission of HAIs [9][10][11][12][13][14][15][16][17][18]. Stethoscopes/phonendoscopes (stethoscopes) are medical devices frequently used in direct contact with patients' skin and can therefore be a vector of infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that computer keyboards (and mouse) can become contaminated with pathogenic bacteria (Schultz et al, 2003;Hartmann et al, 2004;Rutala et al, 2006;Eltablawy and Elhifnawi, 2009;Anastasiades et al, 2009;Shen, 2010;Tagoe and Kumi-Ansah, 2011). In health care settings, it is perhaps Science Publications AJM not unexpected that such microorganisms would contaminate these common work surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The contamination rate of keyboards and mouse was 70.3 and 29.7%, respectively. It was revealed by Hartmann et al (2004) that the highest rate of contamination in patients, rooms was found on keyboards. Schultz et al (2003) found that the tested 100 keyboards in 29 clinical areas for bacterial contamination, 95 from them were positive for microbial contamination.…”
Section: Discussionmentioning
confidence: 99%